[CR-POSSUM and Surgical Apgar Score as predictive factors for patients' allocation after colorectal surgery] - Pinho, S. (2020)
Submitted by José Pereira (jro.pereira@gmail.com) on 2020-03-17T18:53:19Z No. of bitstreams: 1 Escore CR-POSSUM e Índice de Apgar Cirúrgico.pdf: 491768 bytes, checksum: 5fec32f7f95b56043b6d7bbd6be8e5a9 (MD5)